Influence of Donor and Recipient Sex on the Outcome after Pancreas Transplantation. (July 2018) - Messner, Franka; Bösmüller, Claudia; Maglione, Manuel; Riedmann, Marina; Oberhuber, Rupert; Cardini, Benno; Resch, Thomas; Schneeberger, Stefan; Margreiter, Christian
Abstract : Background: Several studies in solid organ transplantation have shown a correlation between gender-match and risk of graft loss. In this study we aimed to analyze the impact of donor and recipient sex on the incidence of pancreas graft loss in our cohort. Methods: We performed a retrospective analysis including all pancreas transplantats performed between January 1979 and December 2016 at the Medical University of Innsbruck. After exclusion of patients with loss to follow-up, 537 patients could be included in the analysis. Median follow-up time was 116 (range 0.6 - 389) months. Statistical analysis was performed using SPSS, a p-value <0.05 was considered statistically significant. Results: Of the 537 pancreas transplantat recipients, 199 (37.1%) were female and 338 (62.9%) were male. In 290 (54%) cases a gender-matched and in 247 (46%) a gender-mismatched transplantation was performed. Kaplan-Meier analysis revealed a significantly superior pancreas graft survival (p = 0.015) in the gender-matched group. Pancreas graft survival at 5 and 10 years was 79, 9% and 63.3% in the gender-matched group compared to 68.1% and 55.9% in the mismatched group. No difference in patient survival could be observed. After division of the different donor-recipient sex constellations only the male-donor-to-male-recipient group had a significant better pancreas graft survival than the female-donor-to-male-recipient group (p = 0.019). Significantly more patients in the male-donor-to-female-recipient group lost their graft (13.2% vs. 4.9%; p=0.005) to acute rejection early after transplantation (mean 27 months). Discussion: Our analysis shows that gender-matched pancreas transplantations lead to a significant better long term graft survival. Early graft loss due to acute rejection is significantly more frequent in the male-donor-to-female-recipient group. Factors, which might influence this result, are a higher recipient and lower donor age in the gender matched group.